Some aspects of industrial finance in India. - Rosen, George (New York : Free Press of Glencoe, 1962)
This book gives a picture of the institutions providing industrial finance in India and outlines the theoretical structure of some of the common institution.
At head of title: The Center for International Studies, Massachusetts Institute of Technology.
Includes bibliography.
ucj, 15/01/2019
Loans
Keywords: Finance; Banks and banking